Antibiotics in corals of the South China Sea: Occurrence, distribution, bioaccumulation, and considerable role of coral mucus. (July 2019) - Zhang, Ruijie; Yu, Kefu; Li, An; Wang, Yinghui; Huang, Xueyong
Abstract: Manmade antibiotics are emerging organic pollutants widely detected in the marine environment. In this study, 14 out of 19 target antibiotics were detected in corals collected from coastal and offshore regions in the South China Sea. The average total antibiotic concentrations (∑19 ABs) in the two regions were similar: 28 ng/g for coastal corals and 31 ng/g for offshore corals, based on dry tissue weight (dw). Fluoroquinolones (FQs) were predominant antibiotics in the coastal corals (mean ∑FQs: 18 ng/g dw), while sulfonamides (SAs) predominated in the offshore corals (mean ∑SAs: 23 ng/g dw). However, corals living in coastal regions tend to excrete more mucus than corals in offshore habitat. We found 53% by average of ∑19 ABs in the mucus of the coastal corals; while in offshore corals, most antibiotics (88% by average) were accumulated in the tissues. In addition, the tissue-mucus mass distribution differs among individual antibiotics. Sulfonamides were mainly accumulated in tissues while fluoroquinolones were present mainly in mucus. The results of this study suggest that mucus played an important role in the bioaccumulation of antibiotics by corals. It may resist the bioaccumulation of antibiotics by coral tissue, especially for the coastal corals. Additionally, corals were compared with other marine biotas in the study area and found to be more bioaccumulative towards antibiotics. Graphical abstract: Image 1 Highlights: The study first studied man-made antibiotic contamination in coral tissue and mucus. Fourteen antibiotics were detected in corals at the level of 10 −2 - 10 1 ng/g dw. Tissue-mucus distribution of antibiotics differs between coastal and offshore corals. Coastal coral mucus may resist accumulation of antibiotics by coral tissue. Corals have high bioaccumulation factors because of their large surface area. Abstract : Man-made antibiotics were first reported in coral tissue and mucus, which paly different roles in bioaccumulation of antibiotics.